Musculoskeletal colloquialisms based on weapons - Agrawal, Anuj (J Clin Orthop Trauma, 2017)
Eponyms and colloquialisms are commonly used in orthopaedic literature and convey a great deal of information in a concise fashion. Several orthopaedic conditions have characteristic clinical or radiologic appearances, mimicking the appearance of certain arms or weapons. Most of these are easy to memorise and recognise, provided the orthopaedic surgeon is aware of the colloquialism and familiar with the appearance of the weapon on which it is based. Unfortunately, many such colloquialisms are based on traditional weapons no longer in current use, and their appearances are not familiar to most orthopaedists, creating confusion and difficulty in understanding them. In this paper, we have reviewed the musculoskeletal colloquialisms based on weapons, including a brief description of the weapon with illustrations, highlighting the importance of the colloquialism in diagnosis or treatment of musculoskeletal conditions.